Social Support and spiritual well-being role in anticipating suicidal ideation during Covid-19 pandemic among Malaysian university students - Ma’rof, Aini Azeqa; Mat Razi, Nur Izzatie; Abdullah, Haslinda (Human Resource Management Academic Research Society, 2021)
Suicidal ideation is prevalent among teenagers and young adults in Malaysia as per reported by the Malaysia Ministry of Health. Meanwhile, there are significant concerns about the possibility of mental health problems occurring during Covid-19 pandemic. Communities have encountered mental health difficulties due to the morbidity, mortality, and mitigation actions associated with Covid-19. However, there has been dearth of empirical research on suicidal ideation during this uncertainty times especially the importance of the coping strategies applied. Thus, the purpose of this cross-sectional study is to examine the association between social support and spiritual well-being on suicidal ideation among young adults. A total of 407 young adults in Lembah Klang Valley participated in this study. The results revealed a significant negative correlation between spiritual well-being and all three types of social support: appraisal support, belonging support, and tangible support. Meanwhile, both suicidal ideation and spiritual well-being identified as significant predictors to suicidal ideation reduction with spiritual well-being as the strongest predictor. Thus, this study suggested that interventions that incorporate social support and spirituality may result in a more positive outcome in the fight against suicidal behavior in young adults. Study implications and recommendations were discussed.